THE AIRLINER CABIN ENVIRONMENT AIR QUALITY AND SAFETY - CHALMERS,TC (Tufts Archival Research Center, 2007)
Missing Page(s); Committee on Airliner Cabin Air Quality Report entitled, “The Airliner Cabin Environment,” recommending a ban on smoking on all domestic commercial flights for the following three reasons: to lessen irritation, decrease discomfort to passengers and crew and reduce potential health hazards to the cabin crew. Discusses different components that make up the air quality inside aircraft such as carbon dioxide and humidity. Recommends and encourages research regarding smoking and air quality for longer and international flights.